Identification of an endangered tree as a new record of Cordia macleodii, with an update of Cordia in West Bengal, India. Issue 1 (2nd January 2018) - Deb, Debal; Li, Bo; Chattopadhyay, Sanjib K.; Ray, Avik
Abstract: We have identified a hitherto undescribed tree, locally known as Sitapatra, which has never been mentioned in any publication of the region's flora. However, by using morphological and molecular analyses, we identified it as Cordia macleodii (Cordiaceae). Several novel traits, never mentioned in previous taxonomic works, were observed and added to the description of the species. We suggest the conservation status of the species to be Critically Endangered, based on the criteria of a critically small population size in a narrow extent of occurrence, and the absence of flowering for 12 years in the past. Subsequently, we have updated here the distribution of Cordia L. in West Bengal, based on records from herbaria and recent publications, as well as our field observations. A distribution map for three native and an exotic species is presented. We find that although the protologue of C. macleodii indicates its type collection from central India, the herbarium record at Royal Botanic Garden, Kew mistakenly shows its type locality as West Bengal.